A global directory of early child development projects - World Bank. (Washington D.C. : World Bank, 2001)
This directory provides an overview of the projects in all regions listed in alphabetical order on early child development (ECD) by the World Bank.
Supported by The World Bank.
rua 19/06/2017
Ref
Keywords: Child development; Child care services; Developing countries